An Electromagnetic Moment in Short Circuits in Electrical Rotating Machines with High-Coercivity Permanent Magnets - Flyur Ismagilov; Irek Khayrullin; Vyacheslav Vavilov; Valentina Ayguzina (Institute of Advanced Engineering and Science, 2017)
This paper presents a computer model of an electrical rotating machine with high-coercivity permanent magnets and research of various short-circuit types in the electrical rotating machine with high-coercivity permanent magnets, including turn-to-turn short circuit. Diagnostic criteria of short circuits are revealed. There are the electromagnetic moment and the magnetic flux density in the stator core back. With comparison the experiment and computer modeling results, it was found that the created computer model is highly accurate and completely repeats the experiment results. The numerical discrepancy between the experimental data and the simulation data is below 5%. The obtained results can be used in practice in the design of the electrical rotating machine with high-coercivity permanent magnets.